Quality Comparison of Naturally and Artificially Ripened Monthong Durian (Durio zibethinus) Fruits Harvested at Various Maturity Stages - Suriyan Supapvanich; Pannipa Youryon (My University, 2022)
The effects of artificial and natural ripening approaches on the quality of ‘Monthong’ durians harvested at various maturity stages were investigated. The fruits were harvested at the maturity stages of 110 (~ 80% maturity), 115 (~ 85% maturity) and 120 (~ 90% maturity) days after anthesis (DAA) and were then artifically ripened by smearing ethephon on peduncle cut surfaces, or were allowed to naturally ripen at room temperature (28±2°C). The ripening period and quality of the ripened durians were determined and compared with the tree-ripened durians (130 DAA). The fruits harvested at 110, 115 and 120 DAA fruits were naturally ripened on days 9, 6 and 4, respectively, after harvesting. All fruits treated with ethephon had ripened on 3 days. Durians at more mature stages had higher pulp yellowness and carotenoid content while the ripening approach had no influence on both parameters. Pulp firmness of naturally ripened durians was lower than artifically ripened fruits. The starch content of the130 DAA fruits was high and similar to durians harvested at 120 DAA, after ripening. The tree-ripened durians had the highest soluble solids content (SSC) and total sugars contents (TSC). The values of SSC and TSC of naturally ripened fruits were higher than those of artificially ripened fruits. Durians harvested at more maturity had higher antixodant capapcity compared to yourger durians. Natural ripening induced antioxidants more than artifical ripening. In conclusion, artificial ripening hastened the ripening period, and the quality of 120 DAA durians after ripening was close to that of 130 DAA fruit.
Keywords: Ethephon; Plant Physiology and Cultivation Studies